Effect Change Concrete Slab Layer Thickness on Rigid Pavement - Almashhadani, G. A.; Al-Sherrawi, M. H. (Engineering, Technology & Applied Science Research, 2022)
Years of research have been devoted to developing a tool to model and analyze the behavior of rigid pavements. A major component of the new design approaches is the three-dimensional Finite Element Method (FEM), which caused a breakthrough in rigid pavement analysis. The current study used FEM to analyze a rigid pavement composed of a concrete slab layer and a subgrade. The impact of the depth of the concrete slab layer on vertical stresses and displacements was studied with the ABAQUS software. Three different thicknesses were chosen, 20, 25, and 28cm, while the thickness of the remaining paving layers remained unchanged. According to the study results, the top of the concrete slab layer had an increase in stress of approximately 88% when its thickness increased from 20 to 28cm, whereas the top of the subgrade layer had a decrease of about 21% in stress. The change in vertical stress at the top of the subgrade layer was 46% for a thickness of 20-25cm and 14.8% for 25-28cm. The percent of the reduction in vertical stress at the top of the concrete slab layer was 13.2% and 1.8% for thicknesses of 20-25 and 25-28cm respectively. Vertical displacement in the middle of the horizontal distance under the tire print was reduced by 14%, 12%, and 24% when the concrete slab layer increased from 20 to 25, from 25 to 28, and from 20 to 28cm respectively.